Methylation status of p16 and p14 genes in locally advanced rectal cancer: potential clinical implication - Kožik, Bojana; Kokanov, Nikola; Knežević-Ušaj, Slavica; Nikolić, Ivan; Davidović, Radoslav; Jovanović Ćupić, Snežana; Krajnović, Milena (Archives of Biological Sciences, 2018)
Paper description: Patients’ response to standard treatment of locally advanced rectal cancer is variable. Many tested molecular parameters have failed to become reliable predictive biomarkers. Promotor hypermethylation of p16 and p14 genes has been frequently reported as an early event in colorectal cancer, but its clinical relevance in rectal cancer, as a distinct entity, has not been established. Combined analysis of p16 and p14 methylation and VEGF expression status could potentially predict a more aggressive phenotype of locally advanced rectal cancer. Aberrant p16 or p14 methylation, together with high vascular endothelial growth factor (VEGF) expression, is significantly associated with a worse treatment response. Abstract: Methylation of p16 and p14 genes is a common event in colorectal cancers; however, their exact role in the prediction of patients’ outcome is unclear. We conducted this retrospective study to evaluate their potential predictive and/or prognostic roles. Methylation-specific PCR was used to examine the methylation status of p16 and p14 in pretherapeutic and preoperative biopsy specimens of 60 patients with locally advanced rectal cancer. The methylation status of the examined genes did not affect the response to preoperative chemoradiotherapy (CRT), recurrence rate and overall survival. However, patients with a simultaneous presence of either p16 or p14 methylation and high vascular endothelial growth factor (VEGF) expression showed a significantly worse response to CRT (p=0.005 and p=0.038, respectively). Moreover, patients with both p16 methylation and high VEGF expression had significantly shorter overall survival (p=0.010), while no such association was found in patients with p14 methylation and high VEGF expression. On the other hand, a subgroup of patients with p16 methylation and low VEGF and high epidermal growth factor receptor (EGFR) expression showed a significantly better response to CRT (p=0.024). The obtained results point to the importance of p16 and p14 methylation analyses in combination with VEGF and EGFR expression, aimed at better predicting treatment response and patient outcome. https://doi.org/10.2298/ABS180316030K Received: March 16, 2018; Revised: June 13, 2018; Accepted: June 13, 2018; Published online: June 19, 2018 How to cite this article: Kožik B, Kokanov N, Knežević-Ušaj S, Nikolić I, Davidović R, Jovanović-Ćupić S, Krajnović M. Methylation status of p16 and p14 genes in locally advanced rectal cancer: Potential clinical implication. Arch Biol Sci. 2018;70(4):681-90.